2018
DOI: 10.35724/mjbm.v1i1.1247
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pelatihan Dan Displin Kerja Terhadap Kepuasan Dan Kinerja Pegawai Dinas Perhubungan Kabupaten Merauke

Abstract: Human resources is the most important asset owned by an organization because The success of an organization is determined by humans. This study aims to determine to determine the effect of Training and  Discipline against Job Satisfaction and Employee Performance of the Office of Transportation of Merauke Regency. This research uses quantitative method. This type of research is descriptive research is causal (causal), to determine the effect of a variable on other variables. In this study using path analysis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…This is in line with the research of Chasanah (2008) and Nongkeng et al (2012) which shows that empowerment has no significant effect on job satisfaction. The results of this study are not in line with research studies conducted by Wang and Lee (2009); Joo and Shim (2010); Akbar et al (2011);Hasmi (2012); Mahayani (2016); and Arifudin et al (2018) which states that empowerment significantly affect job satisfaction. Based on the results of this study, the first hypothesis (H1) namely empowerment affects job satisfaction is rejected.…”
Section: Effect Of Empowerment On Job Satisfactioncontrasting
confidence: 92%
See 1 more Smart Citation
“…This is in line with the research of Chasanah (2008) and Nongkeng et al (2012) which shows that empowerment has no significant effect on job satisfaction. The results of this study are not in line with research studies conducted by Wang and Lee (2009); Joo and Shim (2010); Akbar et al (2011);Hasmi (2012); Mahayani (2016); and Arifudin et al (2018) which states that empowerment significantly affect job satisfaction. Based on the results of this study, the first hypothesis (H1) namely empowerment affects job satisfaction is rejected.…”
Section: Effect Of Empowerment On Job Satisfactioncontrasting
confidence: 92%
“…Several related studies have been conducted previously by Arifudin et al (2018); which states that empowerment has a positive and significant effect on job satisfaction, and job satisfaction has a positive and significant effect on performance. Nongkeng et al (2012); empowerment has a direct and significant effect on organizational commitment.…”
Section: Introductionmentioning
confidence: 99%
“…With a high level of work discipline, it is simpler for an institution to fulfil its objectives; if individuals have work discipline, they will work effectively and on time, prevent anomalies that can harm the institution, and enhance their performance [38].…”
Section: Soft Skills Developmentmentioning
confidence: 99%
“…Previous research on the effect of employee empowerment and organizational learning on employee performance still shows differences in research results. Research conducted by Rasjid & Maramis (2017) , Charli et al (2019) , Fitria & Bindarto (2019) , Aslichatin (2020) , and Habeahan & Khardalin (2020) concluded that employee empowerment had a positive and significant effect on employee performance, while research conducted by Arifudin et al (2018) concluded that employee empowerment had a positive and significant effect on employee performance. Research conducted by Hadi et al (2018) , Mohamad & Nawawi (2020) , Srimulatsih (2021) Wardani et al, (2021) , and Wiyana & Sriathi (2021) prove that organizational learning has a positive and significant effect on employee performance, while research conducted by Astuti & Al-Fansury (2020) concluded that organizational learning has no positive and significant effect on employee performance.…”
Section: Introductionmentioning
confidence: 99%